2015
DOI: 10.1177/0146167215569722
|View full text |Cite
|
Sign up to set email alerts
|

Having Friends and Feeling Lonely

Abstract: Loneliness is a well-known indicator of relationship deficits, with potentially severe consequences on health and well-being (Perlman & Peplau, 1981). Research has used cross-sectional methods to examine behavioral consequences of loneliness (e.g., Cacioppo et al., 2002). However, within-person associations between daily fluctuations in loneliness and subsequent behavioral outcomes have yet to be explored. Using a sample of community-dwelling adults, the authors examined associations between daily loneliness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 48 publications
2
17
0
2
Order By: Relevance
“…Our finding that shame was only predictive of solitary drinking may help explain why studies using between-subjects measures of shame that did not distinguish between solitary and social drinking have generally shown weak or non-existent relationships between shame and drinking frequency or quantity (e.g., Luoma et al, 2017). This pattern of results also aligns with research showing that social and solitary drinking have different antecedents (e.g., Arpin et al, 2015; Mohr et al, 2005), suggesting that future studies of shame and drinking should distinguish between social and solitary drinking.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our finding that shame was only predictive of solitary drinking may help explain why studies using between-subjects measures of shame that did not distinguish between solitary and social drinking have generally shown weak or non-existent relationships between shame and drinking frequency or quantity (e.g., Luoma et al, 2017). This pattern of results also aligns with research showing that social and solitary drinking have different antecedents (e.g., Arpin et al, 2015; Mohr et al, 2005), suggesting that future studies of shame and drinking should distinguish between social and solitary drinking.…”
Section: Discussionsupporting
confidence: 86%
“…relationship conflicts), which could, in turn, trigger drinking. Alternately, shame could lead to social isolation and loneliness, which might then lead people to cope through drinking (Arpin, Mohr, & Brannan, 2015).…”
Section: Shame As An Antecedent Of Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative or positive states of mood were found to be associated with heavier or lighter drinking depending on the individual’s traits and environmental characteristics that these emotions are combined with [57, 61, 63, 72, 82, 86, 93]. Heavy drinking is particularly likely to occur on days when a lot of negative emotion or negative interpersonal events are experienced for individuals who are socially anxious [80], have low self-esteem, high shame or high neuroticism [54, 73, 77], have high social support [43], are less educated [61], have high drinking-to-cope motives [78, 82] or have low drinking to conform motives [78]. In contrast, studies suggested that people with low shame [73], non-students [86], students not affiliated with a sorority [72], men with low attention spans [57] and women with high attention spans [57] are less likely to engage in heavy drinking on days they have negative mood.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, loneliness was considered to be a contributing, maintaining and poor prognostic factor in the development of alcohol abuse and a risk factor for all stages of alcoholism in a recent review [85]. Another study tried to explain these inconsistent findings by assessing transient loneliness and individual drinking behaviors, revealing that loneliness was related to an increase in solitary consumption and a decrease in social alcohol consumption [86]. Unfortunately, we were not able to confirm this potential explanation for the inconsistent association between loneliness and alcohol consumption because the SHS does not include data on social and solitary alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%